2016
DOI: 10.1186/s12913-016-1636-7
|View full text |Cite
|
Sign up to set email alerts
|

Modification of claims-based measures improves identification of comorbidities in non-elderly women undergoing mastectomy for breast cancer: a retrospective cohort study

Abstract: BackgroundAccurate identification of underlying health conditions is important to fully adjust for confounders in studies using insurer claims data. Our objective was to evaluate the ability of four modifications to a standard claims-based measure to estimate the prevalence of select comorbid conditions compared with national prevalence estimates.MethodsIn a cohort of 11,973 privately insured women aged 18–64 years with mastectomy from 1/04–12/11 in the HealthCore Integrated Research Database, we identified di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…Consistent with our results, Lloyd et al found that individuals with more severe obesity were more likely to have a diagnosis coded in the claims data. Nickel et al found that diagnoses recorded in US claims data in 2004 to 2011 had a sensitivity of 17.9% and PPV of 90.9% for obesity in a cohort of women who underwent mastectomy . As in our study, a 1‐year ascertainment period was used for the identification of BMI‐related diagnoses.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Consistent with our results, Lloyd et al found that individuals with more severe obesity were more likely to have a diagnosis coded in the claims data. Nickel et al found that diagnoses recorded in US claims data in 2004 to 2011 had a sensitivity of 17.9% and PPV of 90.9% for obesity in a cohort of women who underwent mastectomy . As in our study, a 1‐year ascertainment period was used for the identification of BMI‐related diagnoses.…”
Section: Discussionmentioning
confidence: 90%
“…Prior studies in the USA and Canada indicate that International Classification of Diseases (ICD) diagnosis codes for obesity recorded in administrative data have a high positive predictive value (PPV; 74%‐91%) but low sensitivity (18%‐19%) . There is limited evidence from a study in women with breast cancer that the sensitivity of administrative diagnosis codes for overweight/obesity may have improved over time in the 2000s . However, this trend has not been confirmed in a broader population, and prior studies have relied on administrative data records from 2011 and earlier.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12,[14][15][16][17] In addition, the caseidentification methods used in recent studies have led to variable performance depending on the existence of other comorbidities, the severity of obesity and the type of health care administrative data. 12,[18][19][20][21][22][23] Accurate case-identification methods for health care administrative databases is essential to minimize classification errors, which can represent a significant form of bias related to the use of administrative databases.…”
mentioning
confidence: 99%
“…The 2 outpatient diagnoses more than 30 days apart is a commonly used method for identifying chronic conditions in claims databases due to the potential for clustering of care immediately following the first diagnosis. 17,18 As anticipated, there was a large degree of overlap between the patient cohorts captured by these 2 algorithms. The timeframe specified between diagnoses as part of the algorithm B criteria may have helped exclude patients who had only a “rule-out” diagnosis recorded in their claims; it may also have increased the accuracy of detection by filtering out patients receiving multiple diagnoses as part of their initial presentation, thus reducing the number of potentially misclassified patients.…”
Section: Discussionmentioning
confidence: 63%